Upregulation of INHBA mediated by the transcription factor BHLHE40 promotes colon cancer cell proliferation and migration. Issue 7 (11th June 2022) - Wang, Jianan; Li, Bo; Yang, Shaohui; Ma, Chenyang; Liu, Kaitai; Chen, Xue; Cui, Wei
Abstract: Background: Colon cancer is highly prevalent, and cell proliferation and migration are major reasons for its progression to malignancy. The upregulation of INHBA, a glycoprotein hormone that regulates the secretion of pituitary hormones, is documented to be oncogenic in numerous cancers, consisting of breast, gastric, and ovarian cancer. Herein, we assessed the role of INHBA in the proliferation along with the migration of colon cancer cells. Methods: TCGA datasets were used to assess INHBA expression and its correlation with prognosis in colon cancer patients. Analyses on JASPAR, PROMO, and ENCODE databases, uncovered high correlation between INHBA and BHLHE40. Western blot and RT‐qPCR analysis were used to determine protein and mRNA levels. Cell transfection inhibited the expression of INHBA and BHLHE40. Cell proliferation rates were determined using CCK8 analysis. Wound healing assays were adopted to explore cell migration. Results: INHBA is markedly elevated in colon cancer tissues along with cells and is a predictive factor for patient's prognosis with colon cancer. INHBA silencing suppressed colon cancer cell proliferation and migration. Furthermore, we confirmed the association of INHBA with BHLHE40 in colon cancer cells. BHLHE40 could directly modulates INHBA expression. Here, we show that BHLHE40 modulates the expression of INHBA, which influences the proliferation, and migration of colon cancer cells. Conclusion: INHBA acts as an oncogene in colon cancer and it can be regulated by the transcription factor BHLHE40. Abstract : TCGA database analysis showed that INHBA was highly expressed in colon cancer. Western blot and qPCR analysis confirmed that INHBA was overexpressed in colon cancer. Analysis on JASPAR, PROMO, and ENCODE databases revealed high correlation of INHBA with BHLHE40 in colon cancer. Then, we show that BHLHE40 modulates the expression of INHBA, which influences the proliferation, and migration of colon cancer cells.